2005
DOI: 10.1002/cncr.21157
|View full text |Cite
|
Sign up to set email alerts
|

Integration of gene expression profiling and clinical variables to predict prostate carcinoma recurrence after radical prostatectomy

Abstract: Objective An inversion polymorphism of approximately 900kb on chromosome 17q21, which includes the microtubule‐associated protein tau (MAPT) gene defines two haplotype clades, H1 and H2. Several small case–control studies have observed a marginally significant excess of the H1/H1 diplotype among patients with Parkinson's disease (PD), and one reported refining the association to a region spanning exons 1 to 4 of MAPT. We sought to replicate these findings. Methods We genotyped 1,762 PD patients and 2,010 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 40 publications
3
120
0
Order By: Relevance
“…Interestingly, when we analyzed a Gene Expression Omnibus database for expression of SPARC in a retrospective cohort of patients, we found that SPARC expression was significantly up-regulated in patients with no recurrence status for at least 5 years after radical prostatectomy ( Fig. 1G) (23). These results strongly suggest that SPARC and Noggin play critical roles in the dormancy of prostate cancer.…”
Section: Nogginmentioning
confidence: 88%
“…Interestingly, when we analyzed a Gene Expression Omnibus database for expression of SPARC in a retrospective cohort of patients, we found that SPARC expression was significantly up-regulated in patients with no recurrence status for at least 5 years after radical prostatectomy ( Fig. 1G) (23). These results strongly suggest that SPARC and Noggin play critical roles in the dormancy of prostate cancer.…”
Section: Nogginmentioning
confidence: 88%
“…Overexpression of the ERG gene alone has been proposed as a surrogate for the presence of the translocation. 4 This is illustrated in Figure 3 by the expression levels of ERG from individual cancers in the dataset of Stephenson et al 12 The cancers exhibiting high levels of ERG expression would be expected to contain ERG gene rearrangements, whereas those with low levels of ERG expression would be expected to lack such rearrangements. However, for cancers with an intermediate level of expression, it is not clear which cancers should be considered to harbor ERG gene fusions and which should be considered to lack the fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Stephenson et al 12 : expression data for the ERG gene determined using Affymetrix U133A human gene array as described previously. Data from each separate cancer sample is presented a black dot.…”
Section: Discussionmentioning
confidence: 99%
“…Unsupervised clustering analyses of prostate cancer expression microarray data sets do not support this view because such analyses have currently failed to identify consistently distinct cancer categories (Singh et al, 2002;Lapointe et al, 2004;Yu et al, 2004;Stephenson et al, 2005) unlike, breast cancer, for example, where separate basal, luminal and ERBB2 subgroups are recognized (Sorlie et al, 2001(Sorlie et al, , 2003. However, a limitation of prostate cancer expression microarray profiles is that they are based on sampling procedures that do not take into account either the welldocumented occurrence of multi-focal disease (Villers et al, 1992;Aihara et al, 1994;Miller and Cygan, 1994;Djavan et al, 1999;Chen et al, 2000;Arora et al, 2004) or the existence of genetic heterogeneity found within individual foci of cancer (Konishi et al, 1995;Mirchandani et al, 1995;Qian et al, 1995;Jenkins et al, 1997;Bostwick et al, 1998;Cheng et al, 1998).…”
Section: Introductionmentioning
confidence: 99%